Case Report: Successful R0 resection in locally advanced retroperitoneal sarcomas - Bael, Peter; Alqtishat, Bayan; Alshawwa, Khaled (Frontiers in Surgery, 2024)
We present a case series of three successfully resected tumors in our center at Al-Makassed Hospital in Jerusalem, Palestine, all of which primarily involved or invaded adjacent structures and needed a multidisciplinary approach to achieve R0 resection.Our first patient is a forty-two-year-old previously healthy female with intermittent attacks of dull aching abdominal pain. Her tumor was a leiomyosarcoma that involved major vessels and other adjacent vital structures. Ultimately, she needed major highly advanced surgery necessitating the need for vascular reconstruction of the IVC, as well as R0 resection. The surgery was performed by a multidisciplinary team of highly specialized surgeons in related fields.Our second case is a 75-year-old female patient with a well-differentiated liposarcoma invading the upper pole of the right kidney, necessitating a nephrectomy. Consequently, this case demanded the interdisciplinary involvement of nephrology.Our third patient is a 59-year-old male with dedifferentiated liposarcoma that involved the spleen, pancreas, and splenic flexure while engulfing the left kidney and ureter. Beyond the removal of the tumor, multiorgan resection was imperative to achieve microscopic margin-free resection. This extensive local spread needed broad collaboration from the medical team and other surgical subspecialties. All surgeries went well, and their outcomes were promising. All patients had an uneventful follow-up and, to date, no recurrence.Invasive retroperitoneal sarcomas of different histological types and clinical stages represent a technical challenge. Careful preoperative investigation and an experienced, dedicated multidisciplinary team of surgeons and non-surgeons from related fields, including vascular, urologic, and hepatobiliary surgeons, are usually needed for a safe and successful R0 resection despite extensive tumor involvement in light of difficulty achieving early diagnosis.